Rudimentary Horn Pregnancy Diagnosed after Laparotomy - Kurabachew Mengistu; Tufa Bobe; Gashaw Tilahun; Kibru Kifle; Dereje Geleta (Case Reports in Obstetrics and Gynecology)
Müllerian abnormalities are present in 0.17% of fertile women and 3.5% of infertile women, and a unicornuate uterus is observed in 0.4% of women. The uterus is normally formed during embryogenesis by the fusion of the two Müllerian ducts. If one of the ducts does not develop, only one Müllerian duct contributes to the uterine development. We report a case of Gravida II, abortion I referred from a primary hospital with a referral paper and sonography stating she had IUFD. She had regular antenatal care follow-up at the primary hospital and had 8 months of amenorrhea. Our ultrasound assessment confirmed the intrauterine fetal demise, but the rudimentary horn pregnancy was missed. Repeated attempts at the induction of labor were tried but unsuccessful. The diagnosis was confirmed at laparotomy. She underwent cesarean section with right intact rudimentary horn removal. A nonviable male fetus with birth weight of 1.2 kg was delivered. Women with this abnormality are asymptomatic and unaware of having a unicornuate uterus. Abdominal pain is the most common presenting symptom with the rudimentary horn, but communicating horn pregnancy is generally asymptomatic in early pregnancy. Early awareness of this rare clinical condition is so crucial especially in developing countries where the availability of new technologies is scarce to explore uterine abnormalities. The patient had uneventful postoperative recovery and was discharged after 3 postoperative days.